2016
DOI: 10.1007/s13361-016-1391-3
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of the Activation Entropy to the Gas-Phase Stability of Modified Nucleic Acid Duplexes

Abstract: Abstract. Tricyclo-DNA (tcDNA) is a sugar-modified analogue of DNA currently tested for the treatment of Duchenne muscular dystrophy in an antisense approach. Tandem mass spectrometry plays a key role in modern medical diagnostics and has become a widespread technique for the structure elucidation and quantification of antisense oligonucleotides. Herein, mechanistic aspects of the fragmentation of tcDNA are discussed, which lay the basis for reliable sequencing and quantification of the antisense oligonucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The results demonstrated that the backbone nature can have strong effects on the dissociation of DNA duplexes. Similarly, a study on tricyclo-DNA conjugates, which are more rigid than the natural counterparts, shows a higher propensity for base loss, which was attributed to changes in the activation entropy (pre-exponential factor) in the rigidified duplexes . Burmistrova et al.…”
Section: Mass Spectrometry Studies Of Nucleic Acid Noncovalent Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated that the backbone nature can have strong effects on the dissociation of DNA duplexes. Similarly, a study on tricyclo-DNA conjugates, which are more rigid than the natural counterparts, shows a higher propensity for base loss, which was attributed to changes in the activation entropy (pre-exponential factor) in the rigidified duplexes . Burmistrova et al.…”
Section: Mass Spectrometry Studies Of Nucleic Acid Noncovalent Complexesmentioning
confidence: 99%
“…Similarly, a study on tricyclo-DNA conjugates, which are more rigid than the natural counterparts, shows a higher propensity for base loss, which was attributed to changes in the activation entropy (preexponential factor) in the rigidified duplexes. 963 Burmistrova et al showed by IMS that (18-bp) 7− duplex rearrangements could occur at collision energies below those required for base loss or strand dissociation. 702 The dynamics of conformational changes of DNA duplexes in the gas phase was also studied by gas-phase FRET.…”
Section: Divalent Cations 4221 Alkaline Earth Metalsmentioning
confidence: 99%